HIV-1 and Bacterial Pneumonia in the Era of Antiretroviral Therapy - Segal, Leopoldo N. (American Thoracic Society, 2011)
Community-acquired pneumonia affects approximately 4 million people in the United States, with 40,000 deaths per year. The incidence is increased about 35-fold in HIV-infected individuals, and this rate has decreased since the antiretroviral era has begun. Bacterial pneumonia has decreased from 5 to 20 cases per 100 person-years to less than 1 to 5 cases per 100 person-years in the era of antiretroviral therapy. HIV-1 infection impairs the function of neutrophils in the lung and infects CD4(+) cells and alveolar macrophages. Opportunistic infections dramatically increase local HIV replication in the lung cells, especially alveolar macrophages and CD4(+) cells. This enhanced replication increases viral mutations and provides opportunities for viral escape from latent reservoirs. Mortality is increased with more comorbidities in this highly susceptible population. Immunization with vaccines is recommended, especially pneumococcal vaccines, although the vaccine itself may stimulate viral replication. Recent studies show that the lower respiratory tract is a microbial reservoir in HIV-infected individuals rather than being a sterile environment, as originally thought. This may provide new opportunities for preventing opportunistic infections in HIV-infected subjects. Bacterial pneumonia presents an ongoing challenge in these high-risk individuals, particularly in studying the functions of the innate and acquired immune response.